Comparative analysis of COVID-19-associated venous thromboembolism outcomes: evolution from 2020 to 2021-2022 - Galeano-Valle, Francisco; Demelo-Rodríguez, Pablo; Alonso-Beato, Rubén; Pedrajas, José María; Fernández-Reyes, José Luis; Chopard, Romain; Sadeghipour, Parham; Hirmerova, Jana; Bikdeli, Behnood; Monreal, Manuel (Journal of thrombosis and thrombolysis, 2024)
Patients with COVID-19 are at an increased risk for venous thromboembolism (VTE). With the advent of vaccinations and novel treatments from 2020 through 2022, the landscape of COVID-19 has evolved. Notably, the effects of such interventions on the outcomes of COVID-19-associated VTE have not been thoroughly examined. Data from the RIETE registry were analyzed to evaluate 90-day VTE-related outcomes (all-cause mortality, major bleeding, and VTE recurrences) in patients with COVID-19-associated VTE. We compared the periods before and after the widespread introduction of COVID-19 vaccines: March to December 2020 (pre-vaccine period) and March 2021 to December 2022 (post-vaccine period). Statistical analysis included mixed-effects parametric survival-time models. Among 1,620 patients with COVID-19-associated VTE, most (74.1%) were identified during 2020 period. The analysis revealed a more than two-fold increase in the risk of death within 90 days (adjusted hazard ratio [HR]: 2.27; 95% confidence interval, CI: 1.18-4.38) and major bleeding (adjusted HR: 2.91; 95%CI: 1.08-7.84) for patients from the 2020 period compared to those from the 2021-2022 period. Inpatient subgroup analysis confirmed the observed mortality differences. The frequency of recurrent VTE was low (1.1 vs. 0.7%, respectively), and did not show significant variation between the two periods. Our research provides a comparative perspective on the clinical outcomes of COVID-19-associated VTE before and after the introduction of vaccines. Our findings reveal a significant decrease in the incidence of 90-day mortality and major bleeding in patients with COVID-19-associated VTE in the 2021-2022 period.
Keywords: žilní tromboembolie; Recurrence; hodnocení rizik; Female; SARS-CoV-2; ženské pohlaví; Venous Thromboembolism; Registries; Time Factors; krvácení; časové faktory; lidé; recidiva; vakcíny proti COVID-19; COVID-19; Aged, 80 and over; Risk Assessment; Risk Factors; Male; Aged; Hemorrhage; rizikové faktory; lidé středního věku; registrace; senioři nad 80 let; senioři; mužské pohlaví; COVID-19 Vaccines; Middle Aged; Humans